Analisis Kriteria Nasabah Mampu terhadap Penerapan Sanksi Wanprestasi pada Produk Pembiayaan KPR Syariah (Studi Kasus pada Bank BSI dan BCA Syariah Kantor Cabang Solo) - Endriasari, Pamella Puritiara; Nashirudin, Muh (Al-Fikru: Jurnal Ilmiah, 2022)
This study aims to determine (1) the criteria for Bank BSI and BCA Syariah Solo Branch Offices in determining default customers on Sharia mortgage financing products are said to be capable or unable, (2) application of sanctions for defaulting customers on Sharia mortgage financing products, (3) conformity of sanctions with DSN-MUI Fatwa No. 17/DSN-MUI/IX/2000 concerning Sanctions for Able Customers who delay Payment. This research is a case study-based qualitative research. The results of the study show that (1) the criteria use the 5C principle, namely Character, Capacity, Capital, Collateral, Condition. However, at Bank BSI the assessment of the customer’s ability is added based on the DBR (Debt Burden Ratio) to reduce the level of risk of default, (2) BSI does not apply fines, while at BCA Syariah applies fines if there are customers who default because they are considered capable, (3) The application of sanctions against defaulting customers on Sharia mortgage financing products at BSI and BCA Syariah is in accordance with the DSN-MUI Fatwa Number 17/DSN-MUI/IX/2000. The sanctions provisions are mutually agreed upon and the sanctions are not included in the bank’s income but in the allocation of benevolence funds or qardul hasan which are realized in the form of Corporate Social Responsibility (CSR) activities.